Preoperative Computed Tomographic Diagnosis of an Aortocaval Fistula Associated with Aneurysm of the Abdominal Aorta - Oda, Takeshi; Hosokawa, Yukio; Zaima, Yasuyuki; Kawara, Takemi; Nomura, Yoriko; Yasunaga, Hiroshi; Shojima, Takahiro (Annals of Thoracic and Cardiovascular Surgery, 2011)
Aortocaval fistula is a rare but life-threatening complication of ruptured abdominal aortic aneurysm. We present a case of an aortocaval fistula with acute right heart failure. The condition was accurately diagnosed before operation by physical examination, echo, and especially by computed tomography (CT), thereby enabling proper planning of the operative strategy. At surgery, not only the infrarenal aorta and common iliac arteries on both sides but the inferior vena cava and iliac veins on both sides were also controlled to avoid massive venous bleeding through the fistula. Aortocaval fistula repair was easy, and conventional bifurcated Dacron graft replacement for abdominal aortic aneurysm was successfully performed. Innovative CT images give us prompt preoperative diagnoses and elaborate surgical strategies.